Analisis Sistem Informasi Manajemen Rumah Sakit (SIMRS) di Rumah Sakit Baladhika Husada Jember - Saputra, Okta; Deharja, Atma; Karimah, Rinda Nurul; Rahagiyanto, Angga (Politeknik Negeri Jember, 2026)
Baladhika Husada Hospital in Jember has implemented a Hospital Management Information System (HMIS) since 2018 to support services such as medical records, inpatient and outpatient care, laboratory, pharmacy, radiology, finance, and emergency care. However, its implementation remains suboptimal due to issues including report formats that do not meet Health Office requirements and incomplete data input by inpatient staff. This study aims to analyze the benefits of HMIS using the HOT-Fit (Human, Organization, Technology) framework. A quantitative cross-sectional design was employed, involving 86 respondents from various managerial levels. Data were collected באמצעות questionnaires and analyzed using SmartPLS 4 with the SEM-PLS approach. The results show that system use is influenced by system quality and user satisfaction, while user satisfaction is influenced by information quality. Organizational environment is affected by organizational structure, and net benefits are influenced by system use, organizational structure, and organizational environment. However, information quality and service quality do not significantly affect system use, and system quality and service quality do not significantly affect user satisfaction. Additionally, user satisfaction does not significantly influence net benefits. These findings highlight the need to strengthen technological aspects to optimize HMIS benefits.